2020
DOI: 10.1111/tmi.13387
|View full text |Cite
|
Sign up to set email alerts
|

Elevated body mass index during pregnancy and gestational weight gain in HIV‐infected and HIV‐uninfected women in Cape Town, South Africa: association with adverse birth outcomes

Abstract: objectives To examine the association between maternal body mass index (BMI) and gestational weight gain (GWG) and adverse birth outcomes in HIV-infected and HIV-uninfected women.methods In an urban South African community, 2921 consecutive HIV-infected and HIVuninfected pregnant women attending primary healthcare services were assessed at their first antenatal visit. A subset of HIV-infected women enrolled in a longitudinal study was assessed three times during pregnancy. All women had birth outcome data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 47 publications
1
16
1
Order By: Relevance
“…Maternal obesity was associated with increased likelihood of having high birthweight and large size for gestational age infants. In the subset cohort, GWG was associated with increased likelihood of spontaneous PTD and high birth weight infants 26 . Obesity during pregnancy is prevalent in this setting and appears associated with increased risk of adverse birth outcomes in both HIV-infected and -uninfected women.…”
Section: Findings To Datementioning
confidence: 90%
“…Maternal obesity was associated with increased likelihood of having high birthweight and large size for gestational age infants. In the subset cohort, GWG was associated with increased likelihood of spontaneous PTD and high birth weight infants 26 . Obesity during pregnancy is prevalent in this setting and appears associated with increased risk of adverse birth outcomes in both HIV-infected and -uninfected women.…”
Section: Findings To Datementioning
confidence: 90%
“…However, factors specific to HIV infection and treatment regimens have also been implicated in influencing the vulnerability of people living with HIV to increased obesity [ 43 ]. Despite the growing number of studies reporting obesity in women with HIV in the general population [ 3 , 5 , 44 , 45 ], there are limited data on GWG trends in this group. One South African study reported that women with HIV experience greater inadequate GWG [ 39 ], however, we found high prevalence of excessive GWG in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In South Africa, almost 70% of women over 15 years are overweight/obese, the highest prevalence in sub-Saharan Africa (SSA) [ 1 ]. Consequently, over 40% of pregnant women are obese at antenatal care (ANC) entry, including those living with human immunodeficiency virus (HIV) on lifelong antiretroviral therapy (ART) [ 2 5 ]. Abundant data show that maternal obesity is associated with metabolic complications in pregnancy, which later increase the risk of a range of NCDs during postpartum period [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although macrosmia has been associated with shoulder dystocia, neonatal and maternal trauma, [49] hypogycaemia, [50] this was not observed in our larger PIMS cohort when we stratified the groups by time of ART initiation (before versus during pregnancy). [51]…”
Section: Discussionmentioning
confidence: 99%